Length of Stay for Patients With Limited English Proficiency in Pediatric Urgent Care. (May 2020) - Patel, Aimy T.; Lee, Brian R.; Donegan, Ravneet; Humiston, Sharon G.
This retrospective chart review compared the length of stay (LOS) of families with limited English proficiency (LEP) versus English-speaking families seen in 3 pediatric urgent care centers (PUCCs). Visits were included for patients aged 2 months to 17 years seen between January 1, 2016, and December 31, 2016, with 1 of 5 primary diagnoses. For each LEP encounter, we randomly selected 3 English-speaking encounters within the same PUCC and diagnosis class. We compared overall LOS between LEP and English-speaking encounters. Of our entire sample, 184 (1.03%) were LEP encounters, of which 145 (78.8%) preferred Spanish. Comparing the LEP visits to 552 matched English-speaking visits, we found a significant difference in average LOS (LEP 85.5 minutes; English-speaking 76.4 minutes) and in prescriptions provided ( P = .005) but not in triaged acuity nor number of medications administered, laboratory or radiological studies, or suction treatments. This study serves as a starting point to better care for patients/families with LEP in PUCCs.